Melt processing of Bi-2212 on MgO and MgO-buffered substrates - Naylor, M; Grovenor, C (1999)
,Bi-2212 thick films have been prepared by full and partial melt processing to investigate the suitability of MgO substrates in polycrystalline, single crystal and buffer layer formats. There is a marked difference in microstructural and electrical properties between thick films on polycrystalline and single crystal MgO substrates. This is attributed to the degree of interaction between the liquid phase and substrate during melting. The thickness of films on single crystal MgO substrates is an important consideration in the optimization of the superconducting transport properties.